THE SPRING VARIATION IN TWO DIMENSIONAL MODELING OF RED BLOOD CELL DEFORMABILITY BASED ON GRANULAR - Ismi Yasifa; Sparisoma Viridi (Program Studi Fisika Universitas Negeri Jakarta, 2019)
The red blood cell membrane has a complex structure and high deformability. Simulation of that complex red blood cell membrane can simpler use granular-based modeling. Red blood cell is modeled consisting of 50 granular particles connected by springs. An i-particle is connected with two of its first nearest particles which are i+1-particle and i-1-particle and with two of its second nearest particles which are i+2-particle and i-2-particle. Each particle has a spring force and forces from internal hydrostatic pressure. Spring force is a product of the spring constant and change of spring length of two particles. Meanwhile, forces of internal hydrostatic pressure is a product of particle diameter and the difference in the outside and inside pressure of red blood cell membrane. In this research, there is variation in spring length and spring constant that can model deformability of three shapes of red blood cell; those are biconcave, ellipse, and circle. This variation in spring length and spring constant for every cell shape in this modeling can also use for other initial cell shapes, which shows that initial cell shapes deform into shape according to variation used.